Evaluation of potential drug interactions in prescriptions of antimicrobials in a hospital in the State of Pará (Research, Society and Development, 2021)
Objective: to evaluate the potential drug interactions of antimicrobials in prescriptions of patients admitted to a hospital in the State of Pará, in 2019. Methodology: This is a qualitative-quantitative, retrospective and cross-sectional study, carried out by collecting data from medical records of patients who used antibiotics and were hospitalized in 2019 in a hospital in Pará. Drug interactions were assessed using the Micromedex database. Results: During the study period, 83% (n = 762) of the patients who were admitted to the institution used antibiotics. There was a male prevalence of 54% (n = 409), the average age was 56 years. 6870 drugs were prescribed, of which 1727 (25%) were antimicrobials, an average of two antibiotics prescribed per patient. A 52% rate (n = 395) of drug interactions was obtained between antimicrobial drugs and other classes. The drug ciprofloxacin had the highest number of interactions, 42% (n = 165), interacting with 12 different drugs. Conclusion: the prescriptions analyzed showed a high index of potential drug interactions. Thus, it is stated that the presence of the pharmaceutical professional inserted in the multiprofessional teams and in the process of evaluating prescriptions in the hospital sector, is of extreme importance and need to reduce risks and increase patient safety in the use of medications.